ABC of jobs people do - Priddy, Roger; Brown, Richard (New York : St. Martin's Press, 2003)
Introduces a different occupation for each letter of the alphabet, and describes what workers from an airline pilot to a zoo keeper do and how they dress, along with the people involved in producing a book.
"Priddy books big ideas for little people."
104829
Keywords: Occupations -- Juvenile literature; Professions -- Juvenile literature; Board books; Juvenile works